The Motivational Aspect of Children’s Delayed Gratification: Values and Decision Making in Middle Childhood - Twito, Louise; Israel, Salomon; Simonson, Itamar; Knafo-Noam, Ariel (Frontiers in Psychology, 2019)
Delayed gratification is the ability to postpone an immediate gain in favor of greater and later reward. Although delayed gratification has been studied extensively, little is known about the motivation behind children’s decisions. Since values are cognitive representations of individuals’ motivations, which serve to guide behavior, we studied the relationship between children’s values and delayed gratification. Two main distinct motivations overlapping with values may underlie this decision: conservation - the desire to reduce uncertainty and preserve the status quo, and self-enhancement - the desire to maximize resources and profit for the self. Accordingly, we hypothesized that conservation values would to relate to children’s preference to hold on to what is given as soon as possible, and that self-enhancement values would relate to children’s preference for delaying gratification. Seven-year old children (N=205) ranked their values with the Picture-Based Values Survey (Döring, Blauensteiner, Aryus, Drögekamp & Bilsky 2010) as part of the Longitudinal Israeli Study of Twins (Avinun & Knafo, 2013). The children also played a decision-making animation game that included delayed gratification decisions. In support of our hypotheses, greater delayed gratification related negatively to conservation values, especially to security and tradition, and related positively to self-enhancement values, especially power and achievement. This is one of the first demonstrations that children’s values relate meaningfully to their behaviors.